Plankton interactions and instability in four tropical reservoirs with different trophic status - Villabona González, Silvia Lucía (Revista de Biología Tropical, 2024)
Introduction: Reservoirs are conceived as a set of interactions in which physical, chemical, and biological instability determine changes in the density of planktonic communities. Objective: To evaluate the instability of phytoplankton and zooplankton, and their interactions with environmental factors in four tropical Andean reservoirs with different trophic status. Methods: Physical and chemical variables and phytoplankton and zooplankton densities were measured between 2010-2018 in the oligotrophic reservoirs Punchiná and San Lorenzo and between 2013 and 2015 in the hypereutrophic reservoir Porce II and in the eutrophic Porce III reservoir (n = 248). The Factor Shaping Community Assemblages (FCA) was used to calculate environmental and biotic instability as well as their interaction. Results: High environmental and biological instability was observed in the studied reservoirs. Oxygen saturation, pH, total nitrogen, water temperature, nitrites, total phosphorus (only for zooplankton) and total solids were the abiotic variables with the greatest contribution to planktonic instability. Particularly, Cryptomonas sp., Aulacoseira sp., Cyclotella sp., Dinobryon sp., Nephrocytium sp., Tetraëdron caudatum and Oscillatoria sp. had the greatest influence on the instability of various rotifer taxa and some copepods. Conclusions: Regardless of trophic state, pH dynamics, nutrients availability, amount of suspended solids and the availability of gases, such as dissolved oxygen, mainly determined the instability of phytoplankton and to a lesser extent that of zooplankton. In the oligotrophic reservoirs, zooplankton instability was mainly influenced by highly palatable algae with no toxicity, and in reservoirs highly enriched, the instability was influenced by algae with low nutritional quality and difficult to ingest and manipulation.